2021
DOI: 10.3390/ijms22105097
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of LL-37 Fragment Mutant-Poly (Lactic-Co-Glycolic) Acid Conjugate against Staphylococcus aureus, Escherichia coli, and Candida albicans

Abstract: Various peptides and their derivatives have been reported to exhibit antimicrobial activities. Although these activities have been examined against microorganisms, novel methods have recently emerged for conjugation of the biomaterials to improve their activities. Here, we prepared CKR12-PLGA, in which CKR12 (a mutated fragment of human cathelicidin peptide, LL-37) was conjugated with poly (lactic-co-glycolic) acid (PLGA), and compared the antimicrobial and antifungal activities of the conjugated peptide with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The CKR12-PLGA hybrid block copolymer showed an estimated CMC value of 12 μM based on the absorbance changes reported in our previous study [ 25 ]. Therefore, the CKR12-PLGA hybrid block copolymer exhibited the behaviour of an amphiphilic block copolymer in aqueous solution and formed a micelle structure.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The CKR12-PLGA hybrid block copolymer showed an estimated CMC value of 12 μM based on the absorbance changes reported in our previous study [ 25 ]. Therefore, the CKR12-PLGA hybrid block copolymer exhibited the behaviour of an amphiphilic block copolymer in aqueous solution and formed a micelle structure.…”
Section: Resultsmentioning
confidence: 95%
“…The procedures for synthesis and structural characterisation by Fourier transform-infrared spectroscopy, 1 H-nuclear magnetic resonance spectroscopy, and haemolytic assays of the CKR12-PLGA hybrid block copolymer have been reported previously [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PI absorption assay showed that Phibilin exerts its killing effect by disrupting the integrity of the plasma membrane of C. albicans ( Figure 3 ), implying that Phibilin is a fungicidal membrane-acting AMP. Besides disrupting the cell membranes, AMPs could also disrupt the morphology of microbial cells, such as CKR12-PLGA ( Mori et al, 2021 ). However, the scanning electron microscopy showed that Phibilin had no effect on the general morphology of C. albicans cells ( Figures 4B–D ).…”
Section: Discussionmentioning
confidence: 99%
“…JCM 7042 were derivatized into 4,4-Dimethyloxazoline (DMOX) and subsequently analyzed by gas chromatography-mass spectrometry (GC-MS) as described previously [35,36] . The position of the double bond of C16:1 was analyzed using the plasma-mediated modification method by liquid chromatography-mass spectrometry (LC-MS) as previously reported [37] . For LC-MS analysis, fatty acid samples were analyzed in the form of free fatty acid (FFA).…”
Section: Identification Of the Chemical Structurementioning
confidence: 99%